2011
DOI: 10.1111/j.1365-2702.2010.03348.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the relationship between adherence with dietary sodium restrictions and health beliefs regarding these restrictions in Irish patients receiving haemodialysis for end‐stage renal disease

Abstract: These findings have implications for the care of patients with end-stage renal disease in that they can provide guidance in terms of developing interventions designed to improve adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 34 publications
8
46
0
2
Order By: Relevance
“…Consistent with the HBM (Janz & Becker, 1984), increased perceived benefits and decreased perceived barriers were found to be related to increased diet adherence. Our findings were partly similar to the study by Walsh and Lehane (2011), showing that the perceived benefits subscale was significantly and positively correlated with adherence to the sodium-restricted diet. Their findings suggested a weak negative but not statistically significant correlation between perceived barriers and adherence to dietary sodium restrictions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the HBM (Janz & Becker, 1984), increased perceived benefits and decreased perceived barriers were found to be related to increased diet adherence. Our findings were partly similar to the study by Walsh and Lehane (2011), showing that the perceived benefits subscale was significantly and positively correlated with adherence to the sodium-restricted diet. Their findings suggested a weak negative but not statistically significant correlation between perceived barriers and adherence to dietary sodium restrictions.…”
Section: Discussionsupporting
confidence: 93%
“…This result was parallel to the results of Welch et al (2006) and Agondi et al (2011). It was interesting that the barriers (less salty food not tasting good and the difficulty of eating out) that most patients perceive and are likely to benefit from tailored interventions in this study are similar to the results found in the U.S. (Welch et al, 2006), Ireland (Walsh & Lehane, 2011), and Brazil (Agondi et al, 2011). Tailored interventions should be designed to reduce these barriers.…”
Section: Discussionsupporting
confidence: 87%
“…To minimize IDWG, hemodialysis patients are advised to restrict their free fluid intake and minimize dietary sodium intake 6, 7 . The literature overwhelmingly demonstrates that, while these lifestyle modifications are essential to the well-being, and survival of hemodialysis patients, adherence is poor 8-14 .…”
Section: Introductionmentioning
confidence: 99%
“…La siguiente barrera de gran peso se relaciona con la dimensión de alimentación, que refleja la mayor problemática para las personas con enfermedad crónica, al igual que en otros estudios, por la situación económica, la falta de habilidades para la preparación de la dieta, pero además por la percepción de una dieta limitante y por falta de conocimientos (7,22,23).…”
Section: Desconfianza Y Temor a Los Estudios De Laboratoriounclassified